Triaminopyrimidine derivatives as transmembrane HCl transporters. Issue 22 (23rd May 2019) - Motloch, Petr; Guerreiro, Ana; Azeredo, Carolina Q.; Bernardes, Gonçalo J. L.; Hunter, Christopher A.; Kocsis, Istvan
Abstract : A series of triaminopyrimidine-based anion transporters has been described, capable of diminishing proton gradients across lipid bilayers at physiologically relevant pH. Abstract : Small synthetic molecules capable of inducing transmembrane anion transport have received a lot of attention as potential anti-cancer agents due to their ability to interfere with intracellular pH homeostasis. A series of triaminopyrimidine-based anion transporters have been synthesised, and they are found to diminish proton gradients across lipid bilayers at physiologically relevant pH. The compounds have p K a values (≈7.2) that allow protonation/deprotonation processes coupled with anion binding/unbinding events in physiologically relevant conditions. Synthetic vesicle transport experiments as well as solid state structures indicate synergistic binding of HCl. Cell assays show that the transporters induce apoptosis in various cancerous cell lines.